Can pecking order theory be implemented in Islamic way? - Masdin, Noorhaizun (2013)
The purpose of this research is to find out or test whether the Small Medium Enterprise financial structures can be implemented in Islamic way. This paper investigate whether the local entrepreneur have a potential to change their approach to access in finance. Samples of 150 SMEs in the local area are participated in this research. Using a structured questionnaire, the data was collected through the entrepreneur located in Beaufort, Sabah. The test conduct to see the result of this research shows that there are strong relationship between entrepreneur agree to expand their business and willingness to be a partner or joint with bank means that, the objective of this study are achieved through the test run.